The Relationship Between Hardiness and Resilience with Mental Disorders in Women in Class IIB - Azqia Azqia; Meutia Zahara; Basri Aramico; Asnawi Abdullah; Marthoenis Marthoenis (GLOBAL HEALTH SCIENCE GROUP, 2025)
Mental health disorders are a significant concern, especially among inmates, as the pressures they experience can lead to dangerous behaviors such as riots or even suicide. This study aims to examine the relationship between hardiness and resilience with mental disorders among female inmates at Class IIB Sigli Penitentiary, Pidie Regency. This observational analytic study uses a cross-sectional design. Data collection was conducted through interviews using questionnaires. The study population consisted of all female inmates at Class IIB Sigli Penitentiary, Pidie Regency. The sample size was calculated using the Slovin formula and selected through accidental sampling, resulting in 60 respondents. Data analysis was performed using logistic regression tests via STATA 17.0. The results indicate a significant relationship between certain factors and mental disorders. Sentence length was significantly associated with anxiety (p=0,038, OR=7,66), where inmates serving more than 5 years had a higher risk of anxiety. Resilience also showed a significant relationship with stress (p=0,051, OR=0,19), with lower resilience individuals at greater risk of experiencing stress. On the other hand, no significant relationship was found between hardiness and depression (p=0,087, OR=0,37), anxiety (p=0,352, OR=2,42), or stress (p=0,086, OR=0,30). The type of case also did not show a significant relationship with depression (p=0,575, OR=0,60), anxiety (p=0,552, OR=2,04), or stress (p<0,145, OR=Omitted). Age and marital status factors were also not significantly related to the mental disorders studied.